A loss of antitumor therapeutic activity of CEA DNA vaccines is associated with the lack of tumor cells' antigen presentation to Ag-specific CTLs in a colon cancer model. Issue 2 (28th January 2015) - Ahn, Euri; Kim, Ha; Han, Kyusun Torque; Sin, Jeong-Im
Abstract: Human colon cancers express carcinoembryonic antigen (CEA). Thus, CEA has been considered as a potential vaccine target for immune therapy against colon cancer. In this study, CEA DNA vaccines plus anti-4-1BB Abs treatment was found to increase Ag-specific CTL activity and antitumor protective responses to MC32 cells. However, CEA DNA vaccines alone displayed few antitumor therapeutic effects while significantly inducing Ag-specific CTL responses. Anti-4-1BB Abs alone displayed antitumor therapeutic effects. Intratumoral electroporation with IL-12 cDNA also showed antitumor therapeutic activity against MC32 cells in a CD8+ T cell-dependent and CEA-non-specific manner, suggesting that established MC32 cells are still susceptible to CTL-mediated killing. Finally, our in vitro assays (Western blot assay, IFN-γ, CTL and apoptosis assays, FACS analysis) and animal studies demonstrated that a lack of antitumor therapeutic activity of CEA DNA vaccines might result from acquisition of tumor cell resistance to Ag-specific CTL-mediated killing through the loss of tumor cells' antigen presentation to Ag-specific CTLs. Taken together, these data show that MC32 cells may resist CEA DNA vaccination by their loss of antigen presentation to CEA-specific CTLs in the therapeutic model.